Research for City Practice. Issue 1 (2nd January 2018) - Acuto, Michele; Aldridge, Rob; Badland, Hannah; Brown, Caroline; Cosgrave, Ellie; Giles-Corti, Billie; Gomez, Luis F.; Grant, Marcus; Hatton, William; Jordan, Helen; Marques, Bruno; McIntosh, Jacqueline; et al.
CITY KNOW-HOW: Human health and planetary health are both influenced by city lifestyles, city leadership, and city development. For both, worrying trends are leading to increasing concern. It is imperative that both become core foci in urban policy. Changing the trajectory will require concerted action. The journal Cities & Health journal is dedicated to supporting the flow of knowledge, in all directions to help make this happen. We want to support communication between researchers, practitioners, policy-makers, communities and decision-makers in cities. This is the purpose of this City Know-how section of the journal. 'Research for city practice' disseminates lessons from research, explaining the key messages for city leaders, communities and the professions involved in city policy and practice. 'City shorts' provide glimpses of what is being attempted or achieved. 'Case studies' are where you will find evaluations of interventions and 'Commentary and debate' helps extend the conversations we are having and develop much needed new thinking. Join in these conversations. In service to strengthening the community of interest, we would like to include many and varied voices, including those from younger practitioners and researchers, connected with supporting health and health equity in everyday urban lives.